Mammals, Serra da Concórdia, state of Rio de Janeiro, Brazil. - Bergallo, H. G.; Esbérard, C. E. L.; Pereira, B. C.; Albuquerque, H, G.; Raíces, D. S. L.; Almeida, J.; Attias, N.; Costa, L. M.; Enrici, M. C.; Jordão-Nogueira, T.; Pessôa, F. S.; Modesto, T. C. (Check List, 2008)
The Atlantic Forest in the state of Rio de Janeiro is extremely fragmented and reduced in its originalextension. Although there are a great number of studies related to the biome, few lists are available for this region. Thepresent study seeks to get information on the mammals of a remnant forest in Serra da Concórdia, an area from whichno information is currently available. The rapid mammal's survey was accomplished by use of pitfalls, live traps,transects, mist nets, and camera traps. We recorded 37 terrestrial species that represent 22.3 % of Rio de Janeiro statemammal species. Among the recorded species, six are endemic of the Atlantic Forest, one is endemic of the state, andeight are in the state list of threatened or presumably threatened species. The area presents great mammal richness andan increasing effort will probably reveal the presence of additional species.